2003
DOI: 10.1126/science.1086916
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced: The Need for a Global HIV Vaccine Enterprise

Abstract: A new collaborative model of research is needed to increase resources, to prioritize the R (ii) to increase the pace, reduce the overlap, and more systematically explore the elements of and delivery systems for vaccines; (iii) to use common standards for the prompt comparative testing of vaccine candidates; (iv) to expand resources for manufacturing vaccine candidates to speed their use in human trials; and (v) to increase the capacity for international clinical trials and to focus this effort toward quickly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(89 citation statements)
references
References 1 publication
0
89
0
Order By: Relevance
“…The rgp120 human Phase III trial was not successful, suggesting that rgp120s may not be viable vaccine candidates in and of themselves (12). However, that rgp120 BaL alone can induce antibodies that neutralize ϳ60% of subtype B HIV-1 isolates provides a beach head from which to work to improve the immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The rgp120 human Phase III trial was not successful, suggesting that rgp120s may not be viable vaccine candidates in and of themselves (12). However, that rgp120 BaL alone can induce antibodies that neutralize ϳ60% of subtype B HIV-1 isolates provides a beach head from which to work to improve the immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…While the first HIV vaccines to reach phase III clinical trials, AIDSVAX B/B [3] and B/E [4], were found to be inefficacious, these large-scale efforts demonstrate the feasibility of conducting safe and ethical human trials of HIV vaccines [5]. With growing international advocacy [6] and increased leadership and coordination of vaccine development efforts through the new Global HIV Vaccine Enterprise [7], HIV vaccine research has gained substantial momentum. Nevertheless, the advent of HIV vaccines will not ensure their acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, comprehensive identification of genes involved in SIV control using functional genomics would likely require hundreds of animals with defined SIV pathogenesis and unprecedented cooperation among the many investigators possessing samples from these animals. Inspiration for this ambitious undertaking can be drawn from other large-scale collaborative efforts recently initiated to answer fundamental questions about HIV and SIV pathogenesis (3,13,14).…”
Section: An Unresolved Question Is Whether Differences In Mamu-b*17-rmentioning
confidence: 99%